How flow and mindfulness interact with each other in mindfulness-based augmented reality mandala coloring activities - Chen, Hao; Liu, Chao; Zhang, Ayuan; Lu, Wen-Qian; Wu, Kan; Chiou, Wen-Ko (Frontiers in Psychology, 2024)
Introduction This study explores the effects of different types of augmented reality (AR) mandala coloring activities on mindfulness and flow in college students. Methods A total of 76 college students participated in the study and were divided into two groups based on their drawing skills: the high-skilled group (n = 38) and the low-skilled group (n = 38). With the help of AR technology, two groups of subjects carried out three mandala coloring experiments with structured mandala, free mandala and cooperative mandala in order. The measurement evaluation in the experimental program included a pre-test before all the experiments (Time 0) and each post-test after three mandala coloring activities (Time 1, Time 2 and Time 3). The balance dimensions of flow and challenge skills of the two groups were measured. Results ANOVA results showed that a single 30-min short-term datura coloring activity did not significantly improve mindfulness (f = 2.339, p = 0.074, η2 = 0.031), but did significantly improve flow (f = 11.918, p = < 0.001, η2 = 0.139). Linear regression results found positive correlations between mindfulness and certain dimensions of flow (e.g., focus on a task, unambiguous feedback, sense of control, challenge – skill balance, and automatic experience). Mindfulness was also found to be negatively correlated with the loss of the self-conscious component of flow. We also found that the free mandala was quite challenging for subjects in the low-skill group, while the teamwork in the cooperative mandala helped them overcome difficulties and cope with challenges. Discussion Flow can be quickly and effectively improved through short AR mandala coloring exercises. The contribution of this study is to provide inspiration and reference for further exploring how AR mandola coloring can improve subjects’ mental state and promote the perfection and development of positive psychological mechanism.